Fetuin-A as a Potential Biomarker of Metabolic Variability Following 60 Days of Bed Rest - Ward, Kiera; Mulder, Edwin; Frings-Meuthen, Petra; O’Gorman, Donal J.; Cooper, Diane (Frontiers in Physiology, 2020)
Background: Fetuin-A is a hepatokine linked to the development of insulin resistance. The purpose of this study was to determine if 60 days head-down-tilt (HDT) bed rest increased circulating fetuin-A and if it was linked to whole body insulin sensitivity (IS). Additionally, we examined whether reactive jump training (RJT) could alleviate the metabolic changes associated with bed rest. Methods: 23 young men (29 ± 6 years, 181 ± 6 cm, 77 ± 7 kg) were randomised to a control (CTRL, n = 11) or RJT group (JUMP, n = 12) and exposed to 60 days of bed rest. Before and after bed rest, body composition and V̇O2peak were measured and an oral glucose tolerance test was performed to estimate IS. Circulating lipids and fetuin-A were measured in fasting serum. Results: Body weight, lean mass and V̇O2peak decreased in both groups following bed rest, with greater reductions in CTRL (p < 0.05). There was a main effect of time, but not the RJT intervention, for the increase in fetuin-A, triglycerides, area under the curve for glucose (AUCG) and insulin (AUCI) and the decrease in Matsuda and tissue-specific IS (p < 0.05). Fetuin-A increased in participants who became less insulin sensitive (p = 0.019). In this subgroup, liver IS and adipose IS decreased (p < 0.05), while muscle IS was unchanged. In a subgroup where IS did not decrease, fetuin-A did not change. Liver IS increased (p = 0.012) while muscle and adipose tissue IS remained unchanged. Conclusions: In this study we report an increase in circulating fetuin-A following 60 days of bed rest, concomitant with reduced IS, which could not be mitigated by RJT. The amount of fetuin-A released from the liver may be an important determinant of changes in whole body IS. In this regard, it may also be a useful biomarker of individual variation due to inactivity or lifestyle interventions.